2021
DOI: 10.1177/10778012211012091
|View full text |Cite
|
Sign up to set email alerts
|

Dating Violence, Sexual Assault, and Sexual Harassment Victimization Among Girls on an Indian Reservation: An Examination of Rates and Risk and Protective Factors

Abstract: We documented the scope and correlates of past 6-month victimization among middle and high school girls on an Indian Reservation. Participants were 102 Native American girls in Grades 6-12. Rates of all forms of past 6-month victimization were higher for high school girls compared with middle school girls. In regression analyses, binge drinking related to higher rates of sexual assault and sexual harassment. Furthermore, connection to culture related to lower rates of sexual harassment, and efficacy to resist … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 73 publications
1
10
0
Order By: Relevance
“…While this finding is consistent with some prior research (Kuyper & Bos, 2017), it differs from the results of other studies that have found sexual minority and non-sexual minority adolescents to have similar reactions to research Kuyper et al, 2012). This finding does not appear to be related to victimization experiences as research examining the link between sexual identity and sexual and dating violence using the current sample did not find significantly higher rates of victimization among sexual minority girls (Edwards et al, 2021). Instead, perhaps it is related to other factors that were not measured in the current study like psychological distress and/or loneliness, both factors that have been linked to research-related upset (Kuyper & Bos, 2017).…”
Section: Discussionsupporting
confidence: 79%
“…While this finding is consistent with some prior research (Kuyper & Bos, 2017), it differs from the results of other studies that have found sexual minority and non-sexual minority adolescents to have similar reactions to research Kuyper et al, 2012). This finding does not appear to be related to victimization experiences as research examining the link between sexual identity and sexual and dating violence using the current sample did not find significantly higher rates of victimization among sexual minority girls (Edwards et al, 2021). Instead, perhaps it is related to other factors that were not measured in the current study like psychological distress and/or loneliness, both factors that have been linked to research-related upset (Kuyper & Bos, 2017).…”
Section: Discussionsupporting
confidence: 79%
“…We also did not include a number of other correlates of IPV, especially culturally specific protective factors, that may reduce risk for IPV among Indigenous college students. Indeed, research with Indigenous adolescent girls documented that connection to one’s Indigenous culture was related to lower risk for IPV (Edwards, Siller, et al, 2022) and participation in traditional cultural activities has been shown to be related to less substance use among Indigenous college students (Greenfield et al, 2018). A number of Indigenous students in the study were also multiracial and future research is needed to gain a fuller understanding of their experiences with IPV.…”
Section: Discussionmentioning
confidence: 99%
“…Findings from the limited body of research that exists suggests that Indigenous girls and women as well as lesbian, gay, bisexual, transgender, queer, and other non-heterosexual or gender diverse (LGBTQ+) Two-Spirit Indigenous peoples experience disproportionately high rates of IPV (Black et al, 2011; Edwards, Siller, et al, 2022; Minnesota Indian Women’s Sexual Assault Coalition). IPV among Indigenous peoples must be considered within the context of colonization and multiple historical traumas (e.g., forced placement in boarding schools, cultural genocide) as well as ongoing traumas and stressors such as racism and poverty (Deer, 2015; Edwards et al, 2020; Smith, 2003; Warne & Lajimodiere, 2015).…”
mentioning
confidence: 99%
“…Children learn about the Lakota virtues from their tiwahe and tiyposaye , which include: humility ( wahwala or wounsiciye ), perseverance ( wowacintanka ), respect ( waohola ), honor ( wayuonihan ), love ( canteognake ), bravery ( woohitike ), fortitude ( cantewasake ), generosity ( wacantognaka ), and wisdom ( woksape ). These virtues are foundations of Lakota culture and contribute to individual, family, and community strengths, and are believed to protect against adversities, including violence (Edwards et al, 2020; Freeman et al, 2016). Thus, a photovoice project that includes multiple generations rather than children or adults separately seemed most consistent with community and cultural values.…”
Section: Introductionmentioning
confidence: 99%